Numerical Analysis of Influential Parameters on the Performance of Vertical-Cylindrical Refinery Furnaces. (2016) - Gunasegran, Sathiya; Azarpour, Abbas
Abstract: An integrated heat transfer modeling of vertical-cylindrical refinery furnaces was carried out to determine the influential parameters on the fired heaters efficiency as well as the process and flue gas temperature variations. The model was developed considering separate sections of the heater encompassing heat of the flue gas. The model was solved by an iterative procedure with initial boundary conditions. The developed model along with its solution was compiled in MATLAB R2013a environment. The parameters involved into the devised model form the basis for the determination of the most influential parameters on the performance of fired heaters. The sensitivity analysis was accomplished via examining five parameters including excess air, tube pitch, inlet air temperature, fuel composition, and fuel flow rate. Model validation reveals that the model results reasonably agree with the experimental data with less than 4% deviation. The sensitivity analysis demonstrated that varying the five influential parameters by 5% from a base case altered the furnace efficiency by 2.69%, 0.93%, 0.22%, 0.21%, and 0.07%, respectively. The devised model can be employed to reduce computing time and technical costs afforded by the use of computational fluid dynamics (CFD) analysis.